100 Jahre Versuchsanstalt für Stahl, Holz und Steine Karlsruhe. Issue 1 (20th December 2022) - Dietsch, Philipp; Sandhaas, Carmen; Ruff, Daniel; Ummenhofer, Thomas
Abstract: Die Berufung von Prof. Dr.‐Ing. Ernst Gaber an die Technische Hochschule Karlsruhe im Jahr 1921 markierte den Startschuss des Prüfraums Gaber, aus dem später die Versuchsanstalt für Stahl, Holz und Steine hervorging. Heute ist die Versuchsanstalt Teil des Karlsruher Instituts für Technologie (KIT) und besteht aus den Abteilungen Holzbau und Baukonstruktion sowie Stahl‐ und Leichtbau. Der folgende Beitrag blickt auf die Geschichte dieser Einrichtung zurück. Abstract: 100 years of KIT Research Centre for Steel, Timber and Masonry The appointment of Prof. Dr.‐Ing. Ernst Gaber at the University of Technology Karlsruhe in 1921 gave the go‐ahead for the Testing Facility Gaber, from which the Research Centre for Steel, Timber and Masonry developed. Today, the research centre is part of Karlsruhe Institute of Technology (KIT) and consists of the departments Timber Structures and Building Construction and Steel and Lightweight Structures. In the following contribution, the history of this institution is presented.